2009
DOI: 10.1186/1746-1596-4-39
|View full text |Cite
|
Sign up to set email alerts
|

Association between the methylenetetrahydrofolate reductase C677T polymorphism and hepatocellular carcinoma risk: a meta-analysis

Abstract: BackgroundMethylenetetrahydrofolate reductase (MTHFR) is a key enzyme in the metabolism of folate. The non-synonymous single nucleotide polymorphism (nsSNP), C677T (Ala>Val, rs1801133), has been verified to impair enzyme activity. The association with cancer susceptibility, including hepatocellular carcinoma (HCC), has also been widely studied. The results, however, were inconsistent. To shed light on the influence of MTHFR C677T polymorphism on HCC, a meta-analysis was conducted.MethodsThe meta-analysis of C6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 43 publications
0
18
1
3
Order By: Relevance
“…colorectal, breast, and gastric cancer). The previous meta-analysis demonstrated an increased risk in homozygote carriers of MTHFR 677TT for gastric, breast, and liver caner, but a decreased risk for colorectal cancer (Jin et al, 2009, Taioli et al, 2009, Dong et al, 2010, Zhang et al, 2010. Bedsides, previous meta-analysis also demonstrated there may be ethnicity-based effects of MTHFR C677T polymorphism on the cancer risk (Jin et al, 2009, Taioli et al, 2009, Dong et al, 2010, Zhang et al, 2010, Zhang et al, 2012.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…colorectal, breast, and gastric cancer). The previous meta-analysis demonstrated an increased risk in homozygote carriers of MTHFR 677TT for gastric, breast, and liver caner, but a decreased risk for colorectal cancer (Jin et al, 2009, Taioli et al, 2009, Dong et al, 2010, Zhang et al, 2010. Bedsides, previous meta-analysis also demonstrated there may be ethnicity-based effects of MTHFR C677T polymorphism on the cancer risk (Jin et al, 2009, Taioli et al, 2009, Dong et al, 2010, Zhang et al, 2010, Zhang et al, 2012.…”
Section: Discussionmentioning
confidence: 95%
“…The previous meta-analysis demonstrated an increased risk in homozygote carriers of MTHFR 677TT for gastric, breast, and liver caner, but a decreased risk for colorectal cancer (Jin et al, 2009, Taioli et al, 2009, Dong et al, 2010, Zhang et al, 2010. Bedsides, previous meta-analysis also demonstrated there may be ethnicity-based effects of MTHFR C677T polymorphism on the cancer risk (Jin et al, 2009, Taioli et al, 2009, Dong et al, 2010, Zhang et al, 2010, Zhang et al, 2012. The present study finds that MTHFR C677T polymorphism is associated with ovarian cancer risk in East Asians but not in Caucasians, and this difference may come from the ethnicity-specific effects of MTHFR C677T polymorphism on cancer risk Though the histological subtypes were not uniformly defined in those included studies in this meta-analysis, no subgroup analyses in specific histological subtypes were feasible.…”
Section: Discussionmentioning
confidence: 99%
“…LINE-1 methylation was positively associated with immune markers in those with high serum folate levels (Ulrich et al 2012 ). Furthermore, there was a nonsignifi cant inverse trend with supplemental vitamin B 6 intakes and LINE-1 methylation (Jin et al 2009 ). In men and women, low folate status measured in blood directly correlated with lower PBMC global DNA methylation, which was specifi c for individuals with the MTHFR 677TT genotype (Friso et al 2002 ).…”
Section: Human Studiesmentioning
confidence: 94%
“…A recent meta-analysis demonstrated a signifi cantly reduced risk associated with the variant CC genotype of the MTHFR A1298C polymorphism compared to the wild-type AA genotype (Qin et al 2013 ). Another meta-analysis revealed a signifi cantly increased risk of liver cancer in individuals with the variant TT genotype of the MTHFR C677T polymorphism compared to the wild-type CC genotype, a risk which was even more pronounced in patients with chronic liver disease (Jin et al 2009 ).…”
Section: Liver Cancermentioning
confidence: 95%
“…23,24 Because of the significant ethnic and geographic variation in the frequency of the C677T variant of the MTHFR gene, researchers have evaluated the Hardy-Weinberg equilibrium of this gene in different populations to study whether allele frequencies remain unaltered across generations. Jim et al's meta-analysis (2009) 25 investigated five Asian and five European or American ethnic populations and confirmed that the genotype distribution in the control group in two studies did not abide by the Hardy-Weinberg principle. Studies by Suzuki et al (2007), 15 Solomon et al (2008), 26 and Kruszyna et al (2009), 27 respectively in Asian, Polish and Indian populations, found that genotype frequencies were in Hardy-Weinberg equilibrium.…”
Section: Introductionmentioning
confidence: 95%